Clock and induction model for somitogenesis - Schnell, S; Maini, P (2000)
After many years of research, somitogenesis is still one of the major unresolved problems in developmental biology. Recent experimental findings show a novel type of pattern formation in which a signal sweeps along the presomitic mesoderm and narrows simultaneously as a new somite is formed. The signal then residues in the posterior half of the new somite, and another wave begins to sweep up from the caudal end. This behaviour is not easily explained by the existing theoretical models. We present a new model for somitogenesis that can account for this behaviour and is consistent with previous experimental observations. Dev Den;217:415-420. © 2000 Wiley-Liss, Inc.